Are bicycle lanes effective? The relationship between passing distance and road characteristics. (September 2021) - Nolan, Jonathan; Sinclair, James; Savage, Jim
Highlights: When vehicles overtake bicycles on roadways, painted bicycle lanes are associated with an increase in the distance of very close passes from 93 cm to 101 cm when compared to similar roads with no bicycle lane. Protected bicycle lanes are 10 times more effective than painted bicycle lanes, and are associated with a change in distance from 93 cm to 166 cm. Where it is not possible to build a protected bicycle lane it is preferable to have a painted bicycle lane than no bicycle lane at all. Other protective factors include wider lanes, single lane roads, smaller vehicles, and the removal of on-street parking. Abstract: An on-road observational study of 162 cyclists was conducted in the Australian cities of Melbourne, Perth, Geelong, and Bendigo. Participants had a distance sensor and two video cameras fitted to their bicycle for two weeks while they cycled on their usual routes, producing 46, 769 events where a motor vehicle passed a bicycle. This was the largest study to-date to record passing behavior on public roads, and a large number of road and traffic attributes that might affect passing distance were included in the analysis. When drivers pass cyclists on roads with painted bicycle lanes, they tend to give more space than on roads without bicycle lanes. This is true even when controlling for the space available on the roadway. Drivers also travel in a more predictable fashion, with less variability in passing distances when a bicycle lane is present. Protected bicycle lanes completely remove the risk of passing events less than 1 m. However, where it is not possible to build a protected bicycle lane it is preferable to have a painted bicycle lane than no bicycle lane at all. Other protective factors include: wider lanes, single lane roads, smaller vehicles, and the removal of on-street parking.